The influence of taxpayer attitudes and understanding of taxation on tax compliance mediated the adoption of an electronic tax system - Sitorus, Jhosua Ricardo; Neni Marlina Br. Purba (SEAN Institute, 2024)
This contribution is given without any direct return to the donor and the tax funds are used to support community welfare as much as possible. The aim of this research is to determine the influence of taxpayer attitudes and understanding of taxation on tax compliance mediated by the implementation of the electronic tax system at KPP Pratama South Batam. The population in this study was 400,034 individual taxpayers registered at KPP Pratama South Batam in 2022 and samples were taken using the Slovin formula, so that a sample of 100 people was obtained. The type of research applied in this research is quantitative. The data source in this research is primary data obtained directly based on respondents' answers from questionnaires published to research subjects. The data analysis techniques used are instrument testing (validity test and reliability test), descriptive analysis, inferential statistical test (Partial Least Square), model measurement test (convergent validity, discriminant validity, composite reliability and Cronbach alpha), structural model test (R-Square (R2), Q2 Predictive Relevance, Goodness Of Fit (GoF) Index, and parametric statistical tests and hypothesis testing). Hypothesis test results (direct influence) taxpayer attitudes have a significant influence on the application of the electronic tax system, understanding of taxation has a significant influence on the application of the electronic tax system, taxpayer attitudes have a significant influence on the application of the electronic tax system, understanding of taxation has a significant influence on the application of the electronic tax system, attitude taxpayers have a significant influence on the application of the electronic tax system, understanding taxation has a significant influence on the application of the electronic tax system and the application of the electronic tax system has a significant influence on the application of the electronic tax system. significant to the existence of taxes. The results of hypothesis testing (indirect influence) of the application of the tax system can mediate taxpayer attitudes towards tax compliance and the significance is 0.003 and the application of the electronic tax system can mediate the understanding of taxation towards electronic tax compliance.